Navigating Educational Disruptions: The Gender Divide in Parental Involvement and Children's Learning Outcomes - Matías Ciaschi; Johanna Fajardo-Gonzalez; Mariana Viollaz (Institute of Labor Economics (IZA), 2024)
This study analyzes the adjustment in time allocation to school support activities by mothers and fathers during the pandemic across 22 Latin American and Caribbean countries, exploring the repercussions on labor market outcomes and children's learning losses. Our analysis reveals that mothers experienced a disproportionate increase in time dedicated to children's educational support compared to fathers, particularly when mothers could work from home. The results suggest that these effects were more pronounced in countries with stringent school closure measures and limited access to in-person instruction. Even as mobility restrictions eased and schools reopened, the additional responsibilities taken on by mothers remained above pre-pandemic levels. Mothers also significantly increased the time spent on non-educational childcare, though to a lesser extent than educational support. We also show evidence indicating a decline in maternal labor force participation and a rise in flexible labor arrangements as mothers allocated more hours to child-related duties. Our study also provides descriptive evidence that children's learning losses were less severe in countries where the gender disparity in pandemic-related school support was greater.
Keywords: I1; J13; J21; 330; time use; childcare; labor; COVID-19; Latin America